The AI Lifespan: Deconstructing the Timeline of AI Medical Training - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into medicine is rapidly transforming healthcare, promising breakthroughs from diagnostic imaging to personaliz...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care